900MPa-grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate as well as manufacturing method and application thereof
By adding Sb and Sn to steel plates and controlling the chemical composition and process parameters, a high-strength Sn-Sb composite acid-resistant and chloride-corrosion-resistant steel plate was prepared, solving the problem of insufficient acid resistance and chloride-corrosion resistance of steel plates in the prior art, and realizing the lightweight and high load-bearing capacity of special heavy-duty containers.
Patent Information
- Application Number
- CN202411554846.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-07
AI Technical Summary
Existing technologies cannot provide a steel plate that is both resistant to acid and chloride ion corrosion, while also possessing high strength and lightweight characteristics, thus failing to meet the requirements for the use of special heavy-duty containers.
By adding Sb and Sn to steel plates and controlling the chemical composition and process parameters, 900MPa grade Sn-Sb composite acid-resistant and chloride ion corrosion-resistant steel plates are prepared. Specific smelting, rolling and cooling processes are used to ensure the high strength and corrosion resistance of the steel plates.
It achieves high strength (yield strength ≥800MPa, tensile strength ≥900MPa) and good resistance to acid and chloride ion corrosion of steel plates, meeting the requirements of lightweight and high load capacity of special heavy-duty containers.
Smart Images

Figure CN119571191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of steel materials and their manufacturing, and in particular to a 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate and a manufacturing method and application thereof. Background Art
[0002] Special heavy-duty containers are specially designed for transporting overweight, oversized or special goods. Compared with standard containers, these containers have special structural designs and technical specifications to meet the loading requirements of specific goods. The use of special heavy-duty containers can reduce the number of loading and unloading operations when goods are transferred between different modes of transportation such as land, water and sea transportation, thereby reducing the resulting process costs. At the same time, it meets the development requirements of the country to reduce the logistics and transportation costs in the market and the development needs of the current logistics market, and is an important part of the future container strategy. The application of special heavy-duty containers has a broad market space and development prospects. Replacing ordinary weathering steel SPA-H with high-strength weathering steel is a key measure to achieve lightweight containers and increase load-bearing capacity. At the same time, the demand for export trade continues to increase, requiring special heavy-duty containers to have a certain resistance to marine atmospheric corrosion, which requires high-strength weathering steel to have a certain acid and chloride ion corrosion resistance while being resistant to industrial atmospheric corrosion.
[0003] The following are the related patents published on improving the corrosion resistance and weather resistance of materials: Publication No. CN110157982A discloses a seawater corrosion-resistant steel plate and its production method, which is characterized by C: 0.08-0.12%, Si: 0.25-0.35%, Mn: 1.0-1.6%, P≤0.012%, S≤0.008%, Cr+Ni+Cu≤1.2%, Sn: 0.025-0.050%, Nb+V+Ti≤0.05%, thickness 20-50mm, annual corrosion thickness ≤2mm under full seawater immersion conditions. The steel plate of this invention is a medium-thick plate with a tensile strength of <750MPa, and only Sn is added in the composition design, without Sb, and is not suitable for environments where acid and chloride ions coexist. Publication No. CN105838996A discloses a 800MPa grade high-strength weathering steel plate and its production method. The chemical composition adds 0.10-0.45% Mo as an element to improve corrosion resistance, and does not add Cr, Ni and Cu commonly added in the weathering steel industry. The alloy cost is expensive and the specific indicators of its corrosion resistance are not mentioned. Publication No. CN114411041A and CN113278879B both disclose a production method for 800MPa grade high-strength weathering steel, but the addition of precious metal Ni content is 0.05%-0.10% and 0.12%-0.30% respectively, and it does not have acid and chloride ion corrosion resistance, and the alloy cost is relatively high. Publication No. CN114182180A discloses a steel plate containing Sn and Sb that is resistant to sulfuric acid and chloride ion corrosion and a method for manufacturing the same. Although the patent has acid and chloride ion corrosion resistance, its strength is relatively low and does not meet the use requirements of special heavy-load containers for high load capacity, nor does it meet the use requirements of special heavy-load containers for lightweight.
[0004] In view of the above problems, the present invention urgently needs to provide a steel plate and a manufacturing method thereof that has the advantages of light weight and high strength while having acid resistance and chloride ion corrosion resistance, so as to overcome the above problems or at least partially solve the above problems. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to propose a 900MPa grade Sn-Sb composite acid-resistant and chloride ion corrosion-resistant steel plate and its manufacturing method and application. The thickness range of the steel plate of the present invention is 2.0mm~6.0mm, and the tensile strength reaches 900MPa, which achieves the purpose of lightweighting and improving the load-bearing capacity of special heavy-load containers. In addition, Sb and Sn are compositely added to the high-strength weathering steel to further improve its acid resistance, and at the same time can resist the corrosion of chloride ions, so that the special heavy-load containers meet the requirements for service in the marine atmospheric environment.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The invention provides a 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate. The chemical components of the steel plate are as follows by weight percentage: C: 0.07%-0.10%, Si: 0.40%-0.60%, Mn: 1.30%-1.70%, P: ≤0.015%, S: ≤0.005%, Cr: 0.70%-1.00%, Ni: 0.05%-0.08%, Cu: 0.25%-0.30%, Ti: 0.13%-0.15%, Sb: 0.08%-0.12%, Sn: 0.10%-0.15%, Alt: 0.020%-0.040%, N≤0.0040%, O≤0.0030%, and the balance is Fe and inevitable inclusions.
[0008] As a further optimization solution of the present invention, the thickness of the steel plate ranges from 2.0 mm to 6.0 mm.
[0009] As a further optimization solution of the present invention, the chemical composition of the steel plate satisfies effective Ti=Ti-3.42N-1.5S≥0.11%.
[0010] As a further optimization scheme of the present invention, the metallographic structure of the steel plate is ferrite+pearlite, the ferrite grain size is 12-13 levels, and a high-density nano-scale TiC precipitation phase is dispersed in the ferrite.
[0011] As a further optimization scheme of the present invention, the yield strength of the steel plate is ≥800MPa, the tensile strength is ≥900MPa, the elongation A is ≥18%, the weathering index I is greater than 6.0, and the corrosion weight loss rate is less than 5.50g / m 2 ·h.
[0012] The present invention also provides a method for preparing a 900MPa grade Sn-Sb composite acid-resistant and chloride ion corrosion-resistant steel plate, which comprises: molten iron pretreatment, converter smelting, LF+RH double refining, continuous casting, slab heating, rough rolling, finish rolling, laminar cooling and coiling process.
[0013] As a further optimization scheme of the present invention, the whole process of molten steel casting adopts a long nozzle and uses special protective slag for weathering steel to protect casting, and is sealed with argon gas; the thickness of the continuous casting slab is 230mm, the slab pulling speed is ≤1.5m / min, and the superheat is controlled at 10℃~25℃; slow cooling treatment is adopted in the crystallizer, and weak cooling method is selected for the secondary cooling water. The production process parameters, pulling speed and abnormal liquid level fluctuations are carried out on the surface of the slab offline for flame cleaning.
[0014] As a further optimization scheme of the present invention, after the slab is taken out of the furnace, high-pressure descaling water is used to blow and remove the surface oxide scale; 3+5 passes of reciprocating rough rolling are adopted, and the temperature of the last rough rolling pass is 1050°C to 1080°C.
[0015] As a further optimization scheme of the present invention, the finishing rolling stage adopts 7 stands for continuous rolling in the austenite non-recrystallization zone, the finishing rolling final rolling temperature is 860-900°C, and after the finishing rolling is completed, laminar water cooling and coiling are carried out, the coiling temperature is controlled at 590-640°C, and the hot rolled coil is air-cooled to room temperature.
[0016] The present invention also provides an application of a 900MPa grade Sn-Sb composite acid-resistant and chloride ion corrosion-resistant steel plate in the preparation of a special heavy-load container.
[0017] The advantages of chemical composition and production process are as follows:
[0018] C (Carbon): As the carbon content increases, the strength of the steel increases. However, the higher the carbon content, the more obvious the peritectic reaction tendency is, and it is easier for air gaps to form between the shell and the wall of the crystallizer. The premature formation of air gaps will lead to uneven shrinkage and uneven shell thickness, and cracks will easily form in weak places, which will easily cause steel leakage accidents and surface quality defects of the ingot. Therefore, the C content is controlled to be 0.07% to 0.10%.
[0019] Si (silicon), Mn (manganese): Si and Mn can both improve the strength of steel, and Si can effectively improve the atmospheric corrosion resistance of steel. However, excessive Si and Mn content will significantly reduce the plasticity and toughness of steel, so the Si content is controlled to 0.40% to 0.60%, and the Mn content is controlled to 1.30% to 1.70%.
[0020] P (Phosphorus): Although P can increase the strength and hardness of steel, it will cause a significant decrease in plastic toughness. Especially at low temperatures, it makes the steel significantly brittle, a phenomenon called "cold brittleness". Cold brittleness makes the cold working and weldability of steel worse. The higher the phosphorus content, the greater the tendency of cold brittleness, so the phosphorus content in steel is strictly controlled. P and Cu are both low melting point elements, which are prone to precipitating brittle phases along grain boundaries and causing surface defects. Therefore, in this application, the P content is strictly controlled to be ≤0.015%.
[0021] Ti (titanium), N (nitrogen), S (sulfur), O (oxygen): S reduces the plastic toughness of steel, easily causes cracks during rolling, is not conducive to welding performance, and reduces corrosion resistance. TiC particles precipitated during layer cooling and coiling after cooling are small and dispersed, and have a strong precipitation strengthening effect, which is also the main reason for the precipitation strengthening of Ti elements. Since the main reason for Ti to exert precipitation strengthening is the large amount of dispersed precipitation of fine TiC, the N and S that will form large particle precipitates are not conducive to the precipitation strengthening of Ti, affecting the effective Ti content in steel. Ti and other alloying elements O, N and S in steel have a strong affinity. The fluctuation of these chemical components during smelting will directly affect the content of effective Ti, resulting in large fluctuations in performance products. Therefore, Ti is controlled to be 0.13% to 0.15%, N≤0.0040%; O≤0.0030%, S:≤0.005%, and Ti-3.42N-1.5S≥0.11%.
[0022] Cr (chromium): Cr is one of the more economical elements for improving the atmospheric corrosion resistance of steel, but too high Cr content will lead to reduced welding performance and affect user use, so the Cr content is controlled to Cr: 0.70% ~ 1.00%.
[0023] Ni (nickel): Ni can increase the self-corrosion potential of the material, reduce the corrosion tendency, and improve the atmospheric corrosion resistance; it can also react with Cu to form a high-melting-point Cu-Ni binary alloy phase, effectively preventing copper embrittlement caused by Cu; but Ni is a precious metal element, and too high a content significantly increases the cost of steel manufacturing, so the Ni content is controlled at 0.05% to 0.08%.
[0024] Cu (copper): The prominent role of Cu in steel is to improve the atmospheric corrosion resistance of ordinary low alloy steel, but the melting point of Cu is only 1083°C. It is easy to precipitate along the grain boundary to form a brittle phase, which has an adverse effect on the high temperature plasticity of the ingot and the toughness and surface quality of the steel plate. Therefore, the Cu content is controlled to be 0.25% to 0.30%.
[0025] Sb (antimony) and Sn (tin): Appropriate amounts of Sb and Sn can resist acid and chloride ion corrosion by forming a dense oxide layer. As the Sb and Sn content continues to increase, the brittle phases precipitated along the grain boundaries gradually increase, reducing the surface energy of the grain boundaries, resulting in insufficient bonding between grain boundaries, inhibiting grain boundary migration, and forcing the formation of grain boundary micropores to offset dislocation accumulation, resulting in the expansion of the third brittle zone of the ingot and greatly increasing the risk of cracks in the ingot. Therefore, the upper limit of the Sb content is controlled at 0.12%, and the upper limit of the Sn content is controlled at 0.15%.
[0026] The molten iron is pretreated with deep desulfurization to [S] ≤ 0.005%, and the refining adopts "LF+RH" double treatment to further reduce the content of non-metallic inclusions and residual N, S and O, improve the cleanliness of the molten steel, and lay the foundation for the effective Ti content of subsequent products ≥ 0.11%.
[0027] The whole process of molten steel casting adopts a long nozzle and uses special protective slag for weathering steel to protect casting, and is sealed with argon. The thickness of the continuous casting slab is 230mm, the slab pulling speed is ≤1.5m / min, and the superheat is controlled at 10℃~25℃. Slow cooling treatment is adopted in the crystallizer, and weak cooling method is selected for the secondary cooling water. The production process parameters, pulling speed and abnormal liquid level fluctuations are carried out on the surface of the slab off the line for flame cleaning. The above measures can effectively suppress the corner cracks of the slab across the wide and narrow surfaces, thereby preventing the occurrence of sawtooth defects on the edge after rolling into hot coils.
[0028] Control the atmosphere in the heating furnace to a reducing atmosphere, with an excess air coefficient of <1.0 and a target of 0.90-0.95, to reduce the formation of an oxide layer on the surface of the slab.
[0029] After the slab is out of the furnace, high-pressure descaling water is used to blow and remove the surface oxide scale. In order to reduce the rolling load of the rolling mill, "3+5" round-trip rough rolling is adopted, and the temperature of the last rough rolling pass is 1050℃~1080℃ to prevent the low slab temperature from causing a sudden increase in rolling force, and at the same time ensure that the temperature of the intermediate billet after rough rolling is outside the sensitive temperature range of thermal cracks. It is forbidden to use edge heaters after rough rolling.
[0030] In the finishing rolling stage, 7 stands are used for continuous rolling in the austenite non-recrystallization zone. The finishing rolling final rolling temperature is 860-900°C. After the finishing rolling, laminar water cooling and coiling are carried out. The coiling temperature is controlled at 590-640°C, and the hot rolled coil is air-cooled to room temperature. The material is rolled in the austenite zone to improve the rolling stability. At the same time, medium-high temperature coiling is used to ensure that a large amount of Ti second phase particles are dispersed and fully precipitated, thereby greatly improving the strength of the material.
[0031] The beneficial effects achieved by the present invention are as follows:
[0032] (1) The present invention limits the steel plate thickness range to between 2.0 mm and 6.0 mm, thereby meeting the lightweight requirements of special heavy-duty containers. At the same time, by controlling the effective Ti to meet Ti-3.42N-1.5S≥0.11%, the adverse effects of N and S on Ti precipitation strengthening are reduced, and the precipitation strengthening effect of TiC is enhanced. In combination with the controlled rolling and controlled cooling process, ferrite + pearlite is obtained, and the ferrite grain size is 12 to 13 levels. A high-density nano-scale TiC precipitation phase is dispersed in the ferrite, and the Ti precipitation strengthening and fine grain strengthening effects are fully exerted. Single Ti strengthening achieves a steel plate with a yield strength of ≥800 MPa, a tensile strength of ≥900 MPa, and an elongation A of ≥18%, thereby meeting the requirements of special heavy-duty containers for high strength and high ductility of the material.
[0033] (2) The present invention calculates the weathering index I of the steel by rationally optimizing the chemical composition of the steel plate and referring to the modified Legault-Leckie formula in the American Society for Testing and Materials standard ASTM G101-01, where I = 26.01 (%Cu) + 3.88 (%Ni) + 1.20 (%Cr) + 1.49 (%Si) + 17.28 (%P) - 7.29 (%Cu) × (%Ni) - 9.10 (%Ni) × (%P) - 33.39 (%Cu) 2 >6.0, weathering index I>6.0. According to TB / T 2375-93 "Test Method for Periodic Immersion Corrosion of Weathering Steel for Railway", the periodic immersion corrosion test was carried out for 72 hours. Compared with the corrosion rate of ordinary weathering steel SPA-H, it is less than 85%, which has good atmospheric corrosion resistance. At the same time, Sn-Sb composite addition is adopted. The steel plate is tested according to the test method specified in JB / T 7901, the temperature is 70℃, and the corrosion solution is 50% H2SO4+3×10 4 mg / L Cl - Under the conditions, the corrosion weight loss rate is less than 5.50g / m 2 ·h. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the corrosion weight loss rate-Sn content change graph.
[0035] Figure 2 This is a metallographic structure diagram of the steel plate of Example 1.
[0036] Figure 3 yes Figure 2 Scanning electron microscope image of high-density nano-sized TiC precipitation phase (white round particles) dispersed in the ferrite.
[0037] Figure 4 yes Figure 2 EDS energy spectrum of high-density nano-sized TiC precipitation phase dispersed in ferrite.
[0038] Figure 5 This is a diagram of a uniformly distributed load of 0.6Pg applied from the inside of the box to the side wall.
[0039] Figure 6 It is a schematic diagram of the simulation test method.
[0040] Figure 7 It is the simulation test result diagram. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.
[0042] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0043] The chemical composition weight percentage of the 900MPa grade Sn-Sb composite acid-resistant and chloride ion corrosion-resistant steel plate provided by the present invention is as follows: C: 0.07%-0.10%, Si: 0.40%-0.60%, Mn: 1.30%-1.70%, P: ≤0.015%, S: ≤0.005%, Cr: 0.70%-1.00%, Ni: 0.05%-0.08%, Cu: 0.25%-0.30%, Ti: 0.13%-0.15%, Sb: 0.08%-0.12%, Sn: 0.10%-0.15%, Alt: 0.020%-0.040%, N≤0.0040%, O≤0.0030%, and the balance is Fe and unavoidable inclusions. The process flow is: molten iron pretreatment → converter smelting → "LF+RH" duplex refining → continuous casting → slab heating → rough rolling → finishing rolling → laminar cooling → coiling.
[0044] The chemical composition of each embodiment and comparative example is shown in Table 1, the main process parameters and mechanical properties of each embodiment and comparative example are shown in Table 2, the atmospheric corrosion resistance of each embodiment and comparative example is shown in Table 3, and the corrosion test data of each embodiment is shown in Table 4.
[0045] Table 1 Chemical compositions of various embodiments and comparative examples of the present invention
[0046]
[0047] Note: The chemical composition test is carried out according to GB / T 4336 "Spark Source Atomic Emission Spectrometric Analysis Method for Carbon Steel and Medium and Low Alloy Steel (Conventional Method)".
[0048] Table 2 Main process parameters and mechanical properties of rolling process of Examples 1 to 3 and Comparative Examples 1 to 2
[0049]
[0050] Note: Mechanical properties test is carried out according to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method".
[0051] Table 3 Atmospheric corrosion resistance of various embodiments and comparative examples
[0052] Relative SPA-H corrosion rate / % Example 1 83 Example 2 82 Example 3 81 Comparative Example 1 83 Comparative Example 2 101 SPA-H 100
[0053] Note: A 72h periodic immersion corrosion test was conducted in accordance with TB / T 2375, with SPA-H, a weathering steel commonly used in containers, as the comparison sample.
[0054] Table 4 Corrosion test data
[0055] <![CDATA[Corrosion weight loss rate, g / m 2 ·h]]> Example 1 5.21 Example 2 5.30 Example 3 5.18
[0056] Note: According to the test method specified in JB / T 7901, at a temperature of 70°C, the corrosion solution is 50% H2SO4 + 3×10 4 mg / L Cl - Test under conditions.
[0057] In the above test results, Table 2 shows that the thickness of the steel plate of each embodiment is between 2-6mm, which can achieve the purpose of lightweight, and the yield strength is ≥800MPa, the tensile strength is ≥900MPa, and the elongation A is ≥18%. It has excellent mechanical properties and improves the load-bearing capacity. Table 3 shows that the corrosion rate of each embodiment relative to SPA-H is <85%, and has good atmospheric corrosion resistance. Table 4 shows that each embodiment has good acid and chloride ion corrosion resistance. This high-strength weathering steel plate not only has good acid and chloride ion corrosion resistance, but also has the advantages of thin thickness, light weight and high strength. It can be used in the manufacture of special heavy-duty container structural parts serving in marine atmospheric environments, and can also be expanded to other fields with acid resistance and chloride ion corrosion requirements.
[0058] According to the test method specified in JB / T 7901, at a temperature of 70°C, the corrosion solution is 50% H2SO4 + 3×10 4 mg / L Cl - Under the same conditions, the influence of Sn content in steel ranging from 0 to 0.15% on its corrosion weight loss rate is shown in Table 5 and Appendix. Figure 1 .
[0059] The corrosion weight loss rate (W) is calculated as follows:
[0060]
[0061] Where: W——Corrosion weight loss rate, g / (m 2 ·h); G0——original weight of the sample, g; G1——weight of the sample after the test, g; a——length of the sample, mm; b——width of the sample, mm; c——thickness of the sample, mm; t——test time, h.
[0062] Table 5 Corrosion weight loss rate of steel containing Sn and Sb
[0063] Sn(%) <![CDATA[Corrosion weight loss rate (g / m 2 ·h)]]> 0 13.33 0.05 13.11 0.10 5.39 0.15 5.18
[0064] Add 0-0.15% Sn to Sb-containing steel, and test according to the test method specified in JB / T 7901, at a temperature of 70°C, with a corrosion solution of 50% H2SO4 + 3×10 4 mg / L Cl - Under the conditions, the corrosion weight loss rate changes with Sn content. Figure 1 When the Sn addition exceeds 0.05%, the corrosion weight loss rate of the steel plate is greatly reduced. When the Sn addition reaches 0.10-0.15%, the corrosion weight loss rate decreases more slowly. Since excessive Sn content has an adverse effect on the high-temperature plasticity of the ingot and the toughness and surface quality of the steel plate, the Sn content of the present invention is controlled at 0.10-0.15% in consideration of the corrosion resistance.
[0065] The metallographic structure of the steel plate of the present invention is ferrite + pearlite, and the ferrite grain size is 12 to 13 levels. Figure 2 The SEM morphology and EDS spectrum of the high-density nano-scale TiC precipitates dispersed in the ferrite are shown in Figure 3 and Figure 4 .
[0066] Application example: The high weathering steel plate prepared in Example 1 is used in special heavy-load containers.
[0067] According to the test method of "China Classification Society-Container Inspection Rules (2012), Chapter 5 Section 2: Test Methods and Requirements", a uniform load of 0.6Pg is applied from the inside of the container to the side wall, and the four bottom corner pieces of the container need to be restrained, see Figure 5 and Figure 6 .
[0068] Depend on Figure 7 It can be seen that the maximum stress reaches 731.50 MPa, which occurs at the junction of the top side beam and the front end. The material of the present invention can meet the strength requirements of special heavy-load containers.
[0069] The above description only provides a specific exemplary description of the present invention. It should be noted that the specific implementation of the present invention is not limited to the above method. As long as various non-substantial improvements are made using the technical concept and technical solution of the present invention, or the technical concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate, characterized in that: The chemical composition of the steel plate is calculated by weight percentage: C: 0.07%-0.10%, Si: 0.40%-0.60%, Mn: 1.30%-1.70%, P: ≤0.015%, S: ≤0.005%, Cr: 0.70%-1.00%, Ni: 0.05%-0.08%, Cu: 0.25%-0.30%, Ti: 0.13%-0.15%, Sb: 0.08%-0.12%, Sn: 0.10%-0.15%, Alt: 0.020%-0.040%, N≤0.0040%, O≤0.0030%, and the balance is Fe and unavoidable inclusions.
2. The 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate according to claim 1, characterized in that: The thickness of the steel plate ranges from 2.0 mm to 6.0 mm.
3. The 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate according to claim 1, characterized in that: The chemical composition of the steel plate satisfies effective Ti=Ti-3.42N-1.5S≥0.11%.
4. The 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate according to claim 1, characterized in that: The metallographic structure of the steel plate is ferrite+pearlite, the ferrite grain size is 12-13 levels, and a high-density nano-scale TiC precipitation phase is dispersed in the ferrite.
5. The 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate according to claim 1, characterized in that: The steel plate has a yield strength of ≥800MPa, a tensile strength of ≥900MPa, an elongation A of ≥18%, a weathering index I>6.0, and a corrosion weight loss rate of <5.50g / m 2 ·h.
6. A method for preparing a 900MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises: molten iron pretreatment, converter smelting, LF+RH double refining, continuous casting, slab heating, rough rolling, finish rolling, laminar cooling and coiling process.
7. The method for preparing the 900MPa grade Sn-Sb composite acid-resistant and chloride-ion-corrosion-resistant steel plate according to claim 6, characterized in that: The entire process of molten steel casting adopts a long nozzle and uses special protective slag for weathering steel to protect casting, and is sealed with argon gas; the thickness of the continuous casting slab is 230mm, the slab pulling speed is ≤1.5m / min, and the superheat is controlled at 10℃~25℃; slow cooling treatment is adopted in the crystallizer, and weak cooling method is selected for the secondary cooling water. The production process parameters, pulling speed and abnormal liquid level fluctuations will cause the slab to be taken off the line for surface flame cleaning.
8. The method for preparing the 900MPa grade Sn-Sb composite acid-resistant and chloride-ion-corrosion-resistant steel plate according to claim 6, characterized in that: After the slab is taken out of the furnace, high-pressure descaling water is used to blow away the surface oxide scale; 3+5 passes of reciprocating rough rolling are used, and the temperature of the last rough rolling pass is 1050℃~1080℃.
9. The method for preparing the 900MPa grade Sn-Sb composite acid-resistant and chloride-ion-corrosion-resistant steel plate according to claim 6, characterized in that: In the finishing rolling stage, 7 stands are used for continuous rolling in the austenite non-recrystallization zone. The final rolling temperature is 860-900°C. After finishing rolling, laminar water cooling and coiling are carried out. The coiling temperature is controlled at 590-640°C, and the hot rolled coil is air-cooled to room temperature.
10. Use of the 900 MPa grade Sn-Sb composite acid and chloride ion corrosion resistant steel plate according to any one of claims 1 to 5 in the preparation of special heavy-duty containers.
Citation Information
Patent Citations
800MPa-grade high-strength and weather-proof steel plate and production method thereof
CN105838996A
Seawater corrosion resisting steel plate and production method thereof
CN110157982A
A thin-gauge high-strength weather-resistant steel plate with atmospheric corrosion resistance of 800MPa and its production method
CN113278879B
Sulfuric acid and chloride ion corrosion resistant steel plate containing Sn and Sb and manufacturing method thereof
CN114182180A
Production method of 800MPa-grade high-strength weathering steel for highway guardrails
CN114411041A